Nanoencapsulated formulation of antibacterial metabolites by soil actinomycete, Nocardia sp. TP5 from Tangkuban Perahu Mountain, West Java, Indonesia, with The ionic gelation technique using Na alginate - Desak Gede Sri Andayani; Elsy Rahimi Chaldun; Desak Gede Tirta Andini (Indonesian Journal of Pharmacy, 2022)
Formulation of nanoencapsulation of antibacterial metabolites from the fermentation of actinomycete strain designed as TP5 has been carried out. Nanoencapsulated formulations performed with Na alginate polysaccharides obtained from brown seaweed can maintain the antibacterial metabolite activity. This study aims to enhance antibacterial activity in nanoencapsulated formulations of antibacterial metabolites with ionic gelation technique using Na alginate and CaCl2. The nanocapsules were prepared by combining the extracellular secondary metabolite Nocardia sp. TP5 with the encapsulation sourced from Na alginate and CaCl2 by ionic gelation technique. The manufacturing methods include fermentation of Nocardia sp. TP5, nanoencapsulated formulation by varying the concentration and ratio of Na alginate, CaCl2, antibacterial metabolites, as well as analysis of nanocapsules. The analysis and characterization of nanoencapsulation using SEM-EDS and PSA included: surface morphology, particle size, chemical constituents, and zeta potential, as well as antibacterial testing against Escherichia coli and Staphylococcus aureus. The results showed that the best-nanoencapsulated formula contains the composition of Na alginate 0.3%, CaCl2 0.06% with a ratio of Na alginate: CaCl2: antibacterial metabolite is 2: 4: 1. The capsule particles formed are evenly distributed over the entire surface with a particle size of 425 nm, zeta potential of -27 mV, and antibacterial activity inhibited the growth of E. coli and S. aureus by 20 and 21 mm, respectively. The variation of the appropriate concentration ratio of Na alginate and CaCl2 greatly affects the uniform nanocapsules size and increases the antibacterial activity.